PANDANGAN DUNIA DALAM NOVEL OLIVER TWIST KARYA CHARLES DICKENS - , FIRDIANSYAH; , Dr. Juliasih, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Oliver Twist by Charles Dickens is a novel which is analysed in this research. The novel consists of the authorâs negative view towards Jews through one of characters named Fagin. The author keep giving bad image towards a Jewish character in the novel as an evil or villainous character. The bad description about the Jew not only on his performance, but also on his words, behavior, and his place. The purpose of this research is to determine world vision of the authorâs social class in Oliver Twist by using theory of genetic structuralism from Lucien Goldmann. Having analysed the structure of the novel and the structure of social structure of English society in nineteenth century, the result of this research shows that there is coherence between them in relation with negative description towards Jews. The structure of Oliver Twist consists of binary oppositions which come to one center opposition, harmony and disharmony. The cathegory of characters in the novel consisits of characters who represent God, cahracters who represent the world, and characters who represent human. The characters who represent human must choose between God and the world, or take both of them at once. Based on cathegorization of characters which is analized, there is different attitude towards Jewish character and non-Jewish characters by the author. The discriminative attitude shows that there is an influence of antisemitism world vision on the author. The negative desciption toward Jews character in Oliver Twist has proved that there is antisemitism world vision as representation of the social classâ world vision of the author, Charles Dickens, who come from middle class of English society in the nineteenth century.